Discernment in 1 Kings 19:1-18: biblical spirituality in works of art - Anne-Marie Bos (Acta Theologica)
This article examines the story of 1 Kings 19:1-18 as a story of discernment. It is a story about a divine-human relational process of Elijah and his God, but also a story that draws the reader into a divine-human relational process. The article discerns a fundamental element of this relational process: a perspective change. This aspect of discernment is indicated in the text along the detour of looking at two works of visual art that refer to the biblical story.